Development and transition of competitive sports to mass sports - Yang, M. X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The 2008 Olympic Games in Beijing have provided an opportunity to show the world the high competition level of sports in China. The event also provides a good opportunity for the development of mass sports. This study aimed to discuss how the current focus on competitive sports in China can be successfully transformed to mass sports. The study will also examine how China will change from a country traditionally emphasizing competitive sports to a country embracing "physical activity for everyone." Methods Assessment of the current status of competitive sports and mass sports in China was undertaken and, combined with a large number of questionnaire responses. Thus, this study investigated the need to develop mass sports and indicate why the current focus of sports in China needs to be changed to mass sports. Results Among people who responded to the questionnaire, 74% of did not know the "Outline of Mass Sports and Fitness Plan"; 67% indicated that there was a need to improve public sports equipment and facilities and 29% believed more attention should be paid to improve the physical activity environment. The development of mass sports in China varies across different regions and there was an imbalanced development between the competitive sports and mass sports. The fact that the development of mass sports was lagging behind has seriously affected the sustainable development and globalization of competitive sports in China. Conclusions Although China had excellent results in the 2004 Olympic Games, there has been a great concern about sustainable development of competitive sports after the 2008 Olympic Games. Competitive sports are not only the combination of science and technology applied in the training, but stem from mass sports. Therefore, greater attention should be paid to mass sports to ensure sport in China progresses into the future.